Modeling of influence factors percentage of governments' rice recipient families based on the best fourier series estimator / Chaerobby Fakhri Fauzaan Purwoko ... [et al.] - Purwoko, Chaerobby Fakhri Fauzaan; Cahyasari, Ayuning Dwis; Aliffia, Netha; Mardianto, M. Fariz Fadillah (2021)
Corona Virus Disease 2019 (COVID-19) pandemic has disrupted the targets of most countries including achieving the Sustainable Development Goals (SDGs), such as minimize poverty and hunger levels. For this reason, Indonesia's Government has implemented the rice for prosperous family program. In this study, the influence factor of the percentage of poor families receiving rice for prosperous family program is modeled based on the Fourier series estimator. The selection of the best Fourier series estimator was based on the smallest Generalized Cross Validation (GCV) value for the oscillation parameter. The results of this study are the estimation of the Fourier Cosine series with oscillation parameter equals to 4 which has a GCV value of 1.2317 x 10-11, MSE of 0.0006807645, and R2 of 99.412%. These results can become recommendations for the government for food security stability and provision of equals social protection for all Indonesian to achieve the SDGs target.